A flexible polymer–nanoparticle hybrid material containing triazole-based Fe(ii) with spin crossover properties for magneto-optical applications. Issue 9 (12th July 2018) - Voisin, Hugo; Aimé, Carole; Vallée, Anne; Coradin, Thibaud; Roux, Cécile
Abstract : Centimeter-scale materials exhibiting solid state-like spin-crossover properties and easy handling under ambient conditions are obtained that preserve their thermochromic behavior over months. Abstract : In the perspective of elaborating functional devices based on inorganic molecular materials, it is important not only to continue research on their synthesis and to understand their properties but also to develop new strategies for their processing and shaping. In this context, we show here that centimeter-scale materials exhibiting solid state-like spin-crossover (SCO) properties and easy handling under ambient conditions can be obtained that preserve their thermochromic properties over months. Combining a triazole-based Fe(ii ) SCO compound with functionalized silica nanoparticles gives rise to nanocomposite soft gels. These gels were used as templates for the formation of a flexible macroporous hybrid silica network via a vapor phase sol–gel process. Further coating with PDMS provided both long-term protection of the material against drying and operationality in aqueous media. Our approach offers new hopes for the development of optical and magnetic devices based on SCO coordination polymers.